Sosialisasi Gemarikan (Gemar Makan Ikan) Usia Sekolah Di MTS Muhammadiyah Sejangkung: Socialization of Gemarikan (Like To Eat fish) School Age in MTS Muhammadiyah Sejangkung - Nurazizah; Bintang Rahasia Ramadhan; Galih Pratama; Trijuli Winarto; Wariah (Pakis Journal Institute, 2022)
Fish is a food ingredient that contains rich proteins, minerals, healthy fats, omega-3s, and vitamins that the human body needs. Nutritional content found in fish is very important in childhood. Therefore, it is necessary to conduct counseling on the importance of the movement of eating fish. The activity was carried out at MTs Muhammadiyah Sejangkung, Sejangkung District, Sambas Regency on September 15, 2022 in the form of counseling with the theme